2020
DOI: 10.1016/j.annepidem.2020.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative incidence and diagnosis of SARS-CoV-2 infection in New York

Abstract: New York State (NYS) is an epicenter of the SARS-CoV-2 pandemic in the United States. Reliable estimates of cumulative incidence in the population are critical to tracking the extent of transmission and informing policies. Methods: We conducted a statewide seroprevalence study in a 15,101 patron convenience sample at 99 grocery stores in 26 counties throughout NYS. SARS-CoV-2 cumulative incidence was estimated from antibody reactivity by first poststratification weighting and then adjusting by antibody test ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
267
6
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(311 citation statements)
references
References 28 publications
25
267
6
2
Order By: Relevance
“…For instance, one study of cumulative incidence of SARS-CoV-2 in New York City through March 29, 2020, showed an incidence of 23%. 10 No PPE shortages occurred at our facility. Washtenaw and Wayne counties, where our VA facility is located and where the largest proportion of study participants reside, reported positive testing rates of 3.27%-5.34% as of July 8, 2020, based on RT-PCR testing.…”
Section: Discussionmentioning
confidence: 81%
“…For instance, one study of cumulative incidence of SARS-CoV-2 in New York City through March 29, 2020, showed an incidence of 23%. 10 No PPE shortages occurred at our facility. Washtenaw and Wayne counties, where our VA facility is located and where the largest proportion of study participants reside, reported positive testing rates of 3.27%-5.34% as of July 8, 2020, based on RT-PCR testing.…”
Section: Discussionmentioning
confidence: 81%
“…The copyright holder for this this version posted October 27, 2020. ; https://doi.org/10.1101/2020.10.25.20216671 doi: medRxiv preprint comparison, a Worldometers calculation estimated an IFR of 1.4% in New York City in May [23], using a prevalence ratio of ten from an early antibody study [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Seroprevalence surveys provide valuable information on the proportion of the population that have ever experienced an infection [7][8][9][10] , however, they can be subject to a number of biases and variable performance of different assays can complicate comparisons of results across studies 11 . Here, we present a model framework that integrates age-specific COVID-19 death data from 45 countries with 22 national-level seroprevalence surveys, providing new insights into the…”
mentioning
confidence: 99%